Influence of Nd:YAG laser on intrapulpal temperature and bond strength of human dentin under simulated pulpal pressure. Issue 1 (January 2016) - Silva, T.; Gonçalves, L.; Fonseca, B.; Esteves, S.; Barcellos, D.; Damião, A.; Gonçalves, S.
Abstract The aim of this study was to evaluate the effects of simulated pulpal pressure (SPP) on the variation of intrapulpal temperature (ΔT ) and microtensile bond strength (μTBS) to dentin submitted to an adhesive technique using laser irradiation. One hundred sound human molars were randomly divided into two groups (n  = 50), according to the presence or absence of SPP (15 cm H2 O). Each group was divided into five subgroups (n  = 10) according to Nd:YAG laser energy (60, 80, 100, 120, 140 mJ/pulse). The samples were sequentially treated with the following: 37 % phosphoric acid, adhesive (Scotchbond Universal), irradiation with Nd:YAG laser (60 s), and light curing (10 s). ΔT was evaluated during laser irradiation using a type K thermocouple. Next, a composite resin block was build up onto the irradiated area. After 48 h, samples were submitted to microtensile test (10 kgf load cell, 0.5 mm/min). Data were analyzed by two-way ANOVA and Tukey tests (p  = 0.05). ANOVA revealed significant differences for ΔT and TBS in the presence of SPP. For ΔT, the highest mean (14.3 ± 3.23 °C)A was observed in 140 mJ and without SPP. For μTBS, the highest mean (33.4 ± 4.15 MPa)A was observed in 140 mJ and without SPP. SPP significantly reduced both ΔT and μTBS during adhesive procedures, lower laser energy parameters resulted in smaller ΔT, and the laser parameters did not influence the μTBS values.